Integrating Artificial Intelligence in English Teaching: Opportunities and Challenges in the Digital Classroom - Julanos; Ida Hendriyani; Ika Wulandari; Imelda C Kamsil (PT. Anagata Sembagi Education, 2025)
This research explores the use of artificial intelligence (AI) in English language teaching, focusing on learning personalization, interaction, and automated feedback. AI allows customization of teaching materials according to students' individual needs, which can improve their understanding. While 73% of students feel AI helps them learn at their own pace, there are concerns from teachers regarding AI's limitations in understanding social context and emotional expressions. In addition, AI improves student interaction through technologies such as chatbots, gamification, and virtual reality, with 80% of students feeling more confident in speaking. However, AI is limited in mimicking human interactions, especially when it comes to sarcasm and cultural context. The study also found that AI is effective in providing automated feedback, but still has shortcomings in assessing accent variations and students' speaking expressions. Challenges to AI implementation also include limited infrastructure, unequal access to technology, and lack of training for educators. Issues related to privacy and ethics arise, with most students and teachers not understanding the use of data in AI systems. Successful AI implementation requires technical support, continuous training, and clear regulations on data protection and technology policy in education.